COVID-19 and the production of knowledge regarding recommendations during pregnancy: a scoping review - Victor Hugo Alves Mascarenhas; Adriana Caroci-Becker; Kelly Cristina Máxima Pereira Venâncio; Nayara Girardi Baraldi; Adelaide Caroci Durkin; Maria Luiza Gonzalez Riesco
Objective to map the production of knowledge regarding recommendations for providing care to pregnant women dealing with the novel coronavirus. Method scoping review, using a broadened strategy to search databases and repositories, as well as the reference lists in the sources used. Data were collected and analyzed by two independent reviewers. Data were analyzed and synthesized in the form of a narrative. Results the final sample was composed of 24 records, the content of which was synthesized in these conceptual categories: clinical manifestations, diagnosis, treatment, working pregnant women, vaccine development, complications, prenatal care, vertical transmission, and placental transmissibility. It is recommended to confirm pregnancy and disease early on, to use technological resources for screening and providing guidance and support to pregnant women. Conclusion recommendations emphasize isolation, proper rest, sleep, nutrition, hydration, medications, and in the more severe cases, oxygen support, monitoring of vital signs, emotional support, and multiprofessional and individualized care. Medications should be used with caution due to a lack of evidence. Future research is needed to analyze the impact of the infection at the beginning of pregnancy and the psychological aspects of pregnant women infected with the virus.